Analisis Kontekstual Surat Al-Anfal Ayat 17: Mengungkap Makna Substantif Perang dan Implikasinya dalam Konteks Kontemporer - Setyarama, Handri (Islamic Religious Education Departement, 2025)
The classical interpretation of the Qur'an has been the primary foundation for understanding the sacred text of Islam for centuries. However, in modern times, criticism has emerged of this approach from contextual commentators, who argue that the Qur'anic text should be understood dynamically, considering the context of the time and location where the revelation was revealed. This article examines the contextualization of Surah al-Anfal verse 17 concerning war through a historical-critical analysis, particularly regarding the asbab al-nuzūl (the reason for the occurrence of the consequences). Second, this verse emphasizes that jihad is not limited to physical warfare but encompasses the struggle against injustice. Third, in the spiritual dimension, this verse teaches submission to God and awareness of God's will. This research recommends applying the ethical and spiritual principles in this verse to address the challenges facing Muslims today, such as justice and the protection of rights..